Polityka władz Jugosławii wobec Kościoła katolickiego w latach 1945–1971 - Wawryszuk, Paweł (Pamięć i Sprawiedliwość, 2017)
The acquisition of power by the communists in Yugoslavia after World War II proceeded in a different way, than in case of other Central and East European countries (except Albania). First of all, Yugoslavia had been liberated mostly by partisans, naturally supported by the Allied Powers. Secondly, taking into account their impact on political reality in the country, they did not follow other communists (e.g. from Poland, Hungary, Bulgaria etc.) in implementing a “transitional period”, but straight away started massive terror against all potential or real political enemies. One of the “natural” enemy of the new government was the Catholic Church (CCh), Institution especially strong in Croatia and Slovenia. Thus, the CCh was oppressed by communists. The authorities used administrative repressions, some of most active priests were killed. The archbishop Alojzije Stepinac, the leader of the Church in Croatia, was sentenced and imprisoned. Gradually, after WW II, communist terror had been substituted by administrative and political repressions. Belgrade had started a kind of political game with Vatican, where the situation of the Church in Croatia was at stake. At this point the pattern was similar to other communist states: the “priests-patriots” associations were established in whole Yugoslavia. However, a lack of success led Josip Broz-Tito, Yugoslav leader, to break off the diplomatic relations with the Holy See in 1952. The diplomatic détente between the Holy See and Belgrade appeared in mid-‘60s, when tough negotiations between states had begun. The agreement, finally signed in 1966, resulted in improvement of the CCh’s position in Croatia and Slovenia. It is worth to be noted, that Vatican was interested in looking for deeper frames of cooperation with Yugoslavia. The main goal was to sign a concordat with a socialist state, what would have a huge impact on Catholicism the whole Eastern Bloc. Apart from that, as Belgrade continued its policy in Non-Aligned Movement, Vatican sought an opportunity to expand its influence in the Third World. Eventually, the concordat was signed in 1970 and in the following year Josip Broz-Tito, as the first communist leader, officially visited pope Paul VI in Vatican. At the end of 1971 a symbolic event for a Church’s history in Croatia took place – “The Croat Spring”. Massive protests in the republic were suppressed by the authorities. Oppositely to clergy in other countries like Poland, the Church in Croatia/Yugoslavia remained passive. This fact had significant consequences, as the Croatian elites almost up to ‘90s felt deep reserve to the Institution.